FINANCIAL LITERACY AND HERDING EFFECTS ON GENERATION Z’S SAVING BEHAVIOUR: EVIDENCE FROM BEKASI DISTRICT - Oom Tikaromah; Maharani Dwi Astuti; Sunita Dasman; Eka Avianti Ayuningtyas (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
A country's economic success is generally measured by its growth rate, which is influenced by public investment and savings. Savings are considered a constructive financial habit because they not only support national economic stability but also help individuals meet future financial needs. This study aims to analyse the role of herding behavior as a mediating variable in the relationship between financial literacy and saving behavior. Data were obtained from 100 Generation Z respondents in Bekasi Regency using purposive sampling techniques. The analysis was conducted using the Partial Least Squares (PLS) approach using SmartPLS 4.0 software. The results showed that financial literacy had a positive effect on saving behavior, while also increasing the tendency for herding behavior. These findings confirm that herding behavior plays a significant mediating role in strengthening the relationship between financial literacy and saving habits. Thus, social factors in the form of peer influence are proven to be an important aspect in shaping Generation Z's financial decisions. The implications of this study emphasise the need for financial education strategies that not only focus on increasing individual knowledge but also consider the social dynamics that encourage sustainable saving behavior.